Upgrading of pinyon-juniper catalytic pyrolysis oil via hydrodeoxygenation. (15th December 2017) - Jahromi, Hossein; Agblevor, Foster A.
Abstract: In this study we discuss hydrodeoxygenation (HDO) of pinyon juniper (PJ) catalytic pyrolysis oil over Ni/SiO2 Al2 O3 catalyst in a batch reactor to improve the physicochemical properties of the oil. The influence of temperature (350–500 °C), reaction time (15–90 min), and initial hydrogen pressure (3.5–10 MPa), on hydrodeoxygenation of PJ pyrolysis oil was investigated. After hydrogenation was completed, gas, coke, and a liquid product of two immiscible phases (aqueous and organic), were obtained. Maximum HDO of bio-oil was achieved at 450° C while the initial hydrogen pressure was 7 MPa and the reaction time was 30 min. Under these conditions, the H/C and O/C atomic ratios changed from 1.29 to 0.29 respectively for bio-oil to 2.36 and 0 for HDO oil respectively. The higher heating value increased from 27.64 MJ/kg of bio-oil to 45.58 MJ/kg of upgraded oil. The water content of organic liquid product was less than 0.05 wt% while it was 1.63 wt% in the feed. The viscosity of upgraded oil was 1.26 cP compared to119 cP for the crude bio-oil. Highlights: Pinyon Juniper (PJ) can be used as a source of producing liquid hydrocarbons. Temperature, hydrogen pressure, and reaction time have significant effect on HDO oil properties. HDO oil obtained at 400 °C had a very similar 13 C NMR spectra to that of commercial gasoline.